Ploidy and genomic group effects on yield components interaction in bananas and plantains across four environments in Nigeria - Baiyeri, K.; Tenkouano, A.; Mbah, B.; Mbagwu, J. (Elsevier, 2000)
Thirty-six Musa genotypes, comprising the three major genomic groups (AAA, AAB, ABB) and their hybrids, were evaluated in four environments in Nigeria. Multiple correlation and path coefficient analysis was performed on phenological and yield traits. Bunch weight was more associated with phenological traits in triploid Musa, especially in resource-poor environments. In tetraploid Musa hybrids, bunch weight was consistently correlated with fruit traits. Path coefficient analysis demonstrated that, as expected, bunch weight was essentially determined by the number and weight of fruits. Phenological traits such as plant height and number of days to flowering had low direct effects on bunch weight, but their indirect effects via fruit traits were high. We conclude that ideotype breeding should aim at increasing the number of fruits and the fruit weight regardless of the target environment. Additional gains could be achieved by adopting crop management options that improve the expression of these traits.